2021
DOI: 10.3390/jcm10225412
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Pulmonary Embolism in Patients with Paralysis and Deep Venous Thrombosis

Abstract: Background. Venous thromboembolism is a frequent complication and an important cause of death in patients with paralysis. We aimed to investigate predictors of pulmonary embolism (PE) and the impact of PE on the survival of patients with paralysis in comparison to those with deep venous thrombosis or thrombophlebitis (DVT). Methods: Patients were selected by screening the German nationwide inpatient sample (2005–2017) for paralysis, and were stratified for venous thromboembolism (VTE) and the VTE-sub-entity PE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Inclusion criteria consisted of the following: (1) patients diagnosed with a traumatic fracture; (2) patients who underwent fasting blood glucose, routine blood tests, and coagulation tests at admission; (3) patients who were examined via whole-leg compression ultrasound to detect DVT at admission. Exclusion criteria comprised the following: (1) patients with an open wound or neurovascular injury; (2) patients with unstable vital signs at admission; (3) patients with combined injuries and multiple fractures; (4) patients with a history of PE or DVT; (5) patients with tumors or who were pregnant; (6) patients who underwent long-term anticoagulation; and (7) patients with incomplete clinical data. The selection process is illustrated in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inclusion criteria consisted of the following: (1) patients diagnosed with a traumatic fracture; (2) patients who underwent fasting blood glucose, routine blood tests, and coagulation tests at admission; (3) patients who were examined via whole-leg compression ultrasound to detect DVT at admission. Exclusion criteria comprised the following: (1) patients with an open wound or neurovascular injury; (2) patients with unstable vital signs at admission; (3) patients with combined injuries and multiple fractures; (4) patients with a history of PE or DVT; (5) patients with tumors or who were pregnant; (6) patients who underwent long-term anticoagulation; and (7) patients with incomplete clinical data. The selection process is illustrated in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“… 5 It is well known that DVT is the main risk factor for PE. 6 Therefore, early prediction and intervention of DVT in high-risk patients with traumatic fractures have considerable clinical significance. Previous studies have mostly focused on preoperative DVT, while less attention has been paid to DVT that might have occurred at admission.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of early PE after trauma can be as high as 10%-42% (5). Studies have confirmed that VTE is a major risk factor for PE (6). Therefore, being able to predict deep vein thrombosis (DVT) in patients with traumatic fracture at the time of admission for implementing appropriate interventions is of considerable clinical importance.…”
Section: Introductionmentioning
confidence: 99%
“…VTE is a complex multifactorial disease that integrates genetics and many well-recognized traditional risk factors, such as hormone replacement therapy, cancer, heart failure, chronic obstructive pulmonary disease, trauma, surgery, immobilization, and paraplegia, have been identified. [3][4][5] In a retrospective cohort study, Stewart and Kline found that four components of metabolic syndrome: hyperlipidemia, hypertension, hyperglycemia, and abdominal obesity, were statistically associated with VTE. 6 Recently, some observational studies have also confirmed the correlation between obesity and VTE.…”
Section: Introductionmentioning
confidence: 99%